Assessment of compliance to standard precautions among nurses using the Health Belief Model - Rusli, Noer Triyanto; Mansyur, Muchtaruddin; Kekalih, Aria; Sulistomo, Astrid; Werdhani, Retno Asti (Universa Medicina, 2020)
BACKGROUNDThe application of Standard Precautions (SP) has become a significant challenge for healthcare workers, especially in developing countries, endangering their safety and increasing their exposure to blood-related pathogens. This study was aimed at exploring the factors related to nurses’ compliance with the practice of SP.METHODSA cross-sectional study was conducted on 120 nurses working at a hospital in Palembang. Health Belief Model components of the subjects were recorded through questionnaires. A 12-point observation form assessed the nurses’ SP compliance. Multiple logistic regression models were used to explore factors associated with nurses’ compliance.RESULTSThe results showed that 56.7% of participants had good compliance, although the five moments of hand hygiene still needed to be improved. The study revealed that the proportion of the operating room and emergency room nurses who complied with the SP was larger than the proportion of those who worked at the other wards (OR=2.57, 95% CI 1.51-4.36). The nurses who had received training also showed a larger proportion of compliance with SP than those who had not been trained (OR=2.70, 95% CI 1.07-6.79).CONCLUSIONNurses’ behavior to SP was significantly associated with the adequacy of the training and work unit. It is suggested that the practice of SP was also influenced by enabling factors and subjective norms. Adequate training of nurses, provision of infection prevention equipment, and assessment of occupational exposures need to be introduced.